2015
DOI: 10.1038/pr.2015.270
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of metabolic syndrome by a high intake of energy-dense nutrient-poor snacks in Iranian children and adolescents

Abstract: Background: Our aim was to investigate the relationship between metabolic syndrome (MetS) and energy-dense nutrient-poor solid snacks intakes during 3.6 y of follow-up among children and adolescents. Method: This population-based longitudinal study was conducted within the framework of the Tehran Lipid and Glucose Study, on 424 MetS free subjects, aged 6-18 y. Data on consumption of energy-dense nutrient-poor solid snacks, sweet and salty snacks, were collected at baseline (2006)(2007)(2008). Logistic regressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
16
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 46 publications
(39 reference statements)
3
16
2
Order By: Relevance
“…It is essential that dietary education be conducted to encourage the intake of a healthy diet, and to investigate whether this leads to improvements in motor skills. protein-energy ratios [22]. The present study also found that sh and meat intake was positively correlated with NPFT scores in both boys and girls.…”
Section: Discussionsupporting
confidence: 80%
“…It is essential that dietary education be conducted to encourage the intake of a healthy diet, and to investigate whether this leads to improvements in motor skills. protein-energy ratios [22]. The present study also found that sh and meat intake was positively correlated with NPFT scores in both boys and girls.…”
Section: Discussionsupporting
confidence: 80%
“…A number of dietary factors have been implicated in the pathogenesis of NAFLD with a recent focus on dietary carbohydrates, sugar-sweetened beverages and the monosaccharide fructose in particular [12]. Increasing consumption of energy-dense nutrient-poor snacks might be due to several factors, including inappropriate eating habits, poor nutrition knowledge, media advertising and easy access to them; most of these are attributed to changes in dietary habits in keeping with the shift from the traditional to the western lifestyle [13]. Unhealthy snacks, on the other hand, usually substitute healthy snacks, including fruits and dairy, which are a part of low-energy high-nutrient diet [14].…”
Section: Discussionmentioning
confidence: 99%
“…To date, no other studies have investigated the relation of unhealthy snack consumption and subclinical atherosclerosis among children and adolescents. However, some limited controversial findings investigated the association of unhealthy snacks and CVD risk factors with metabolic syndrome [19, 22, 23]. Our previous study showed consumption of unhealthy snacks increased the risk of the incident metabolic syndrome and hypertension [22], findings in contrast to those of a cross-sectional study performed in the United States, that candy consumption did not have a relationship with blood pressure and lipid profiles of both children and adolescents [23], which is in line with results of the IDEFICS study which found that sweets decreased the CVD risk score by 48% and had a protective effect on CVD risk factors [19].…”
Section: Discussionmentioning
confidence: 99%